The impact of triglyceride-glucose index on the prognosis of post-PCI patients–a meta-analysis - Wang, Yi-Fei; Kong, Xiao-Han; Tao, Hui-Min; Tao, Li (Frontiers in Cardiovascular Medicine, 2024)
Background Previous research has demonstrated the validity of the triglyceride-glucose (TyG) index as a robust measure of insulin resistance (IR) and its association with coronary artery disease (CAD). The objective of this study is to elucidate the relationship between the TyG index and the prognosis of patients underwent percutaneous coronary intervention (PCI) through a comprehensive systematic review and meta-analysis. Our goal is to provide a thorough analysis of the available evidence to offer more clarity on this association. Methods A systematic and thorough search was carried out in the PubMed, Embase, Cochrane Library, and Web of Science databases, covering studies published in English from the beginning until October 1, 2023. The focus of the search was to gather relevant studies pertaining to the occurrence of major adverse cardiovascular events (MACE). To address the variability among the included studies, random or fixed effect models were utilized to summarize the hazard ratios (HR). In cases where heterogeneity was detected, subgroup or sensitivity analyses were performed to explore potential sources. To evaluate publication bias, the Egger or Begg test was employed. Results This study incorporated a total of 17 studies. Individuals with the highest TyG index exhibited an elevated risk of major adverse cardiovascular events (MACEs) compared to those with the lowest TyG index (HR = 1.69; 95% CI: 1.47–1.95; P < 0.001). When analyzing the TyG index as a continuous variable, each standard deviation increase was associated with an HR of 1.60 (95% CI: 1.48–1.73; P < 0.001). Moreover, in patients diagnosed with acute coronary syndrome (ACS), higher TyG index levels showed a trend of increased risk of MACE (HR = 1.54; 95% CI: 1.27–1.86; P < 0.001). Furthermore, an elevated TyG index was found to be associated with a higher risk of in-stent restenosis (HR = 1.62; 95% CI: 1.29–2.03; P < 0.001), new-onset atrial fibrillation (HR = 2.97; 95% CI: 2.10–4.06; P = 0.014), and a reduction in quantitative flow ratio (HR = 1.35; 95% CI: 1.101–1.592; P = 0.005). Subgroup analysis indicated the risk of MACE was comparable between varied durations of follow-up (P = 0.11). Furthermore, regression analysis revealed that the positive association between TyG index and the risk of MACE did not differ between individuals with or without diabetes (P = 0.23). Conclusion An increase in the TyG index may lead to a higher vulnerability to major adverse cardiovascular events (MACE) in patients underwent PCI and there was no significant difference in the risk of major adverse cardiovascular events (MACE) between diabetic and non-diabetic individuals.